The Correlation of Collateral Circulation and Age during Acute Ischemic Heart Disease - Chigogidze, Maia; Sharashidze, Nino; Pagava, Zurab; Taboridze, Iamze (European Scientific Journal, ESJ, 2020)
BackgroundË Coronary collaterals (CC) are alternative sources of blood supply to myocardium jeopardized by Ischemia. Aim: To investigate the dependence and influence of collateral circulation on age during acute ischemic heart disease. Methods: Analysis shows that 673 patients were studied from the SamgoriMedi Clinic (Tbilisi, Georgia) aged 27â€“ 94 years (64.7+11.48) with acute coronary syndromes. Basic medical data such as sex, age, cardiovascular risk factors, angina pectoris, revascularization history, echocardiography, and laboratory data were obtained from the patientâ€™s medical records. CC vessels were graded according to the Rentrop grading system of 0 to 3. ResultsË The development index of collateral circulations visibly increases with age. Average age increases accordingly as follows: rentrop 0 - 62.85+12.01, rentrop 1 - 64.90+10.79, rentrop 2 - 66.84+10.49, and rentrop 3 - 69.04+9.68 (p<0.0001). There is positive significant correlation between the development of collateral circulation and age groups r=0.170**, p<0.001. The cases of female sex, hypertension, acute MI without ST elevation, CABG frequency (also EF% - 35-45%, <35%), and multiple vessel coronary lesion are noticed to increase with age, while the male sex and EF (ejection fraction) >45% cases decreases with age. Conclusion Collateral circulation shows significantly positive correlation with age and female sex. However, it should be mentioned that in elderly patients with a high ejection fraction and normal diastolic function, the development of collateral vessels is low.